2019
DOI: 10.1016/j.drugalcdep.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between childhood abuse and substance misuse problems is mediated by substance use coping motives, in school attending South African adolescents

Abstract: HighlightsChild abuse linked to drug problems in South African school attending adolescents.Drug use coping motives mediated this relationship.Prevention programs should target drug use coping motives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 64 publications
2
33
0
Order By: Relevance
“…Mood induced drug choice was more replicably associated with coping motives than with dependence severity or psychiatric symptoms, suggesting that coping motives is the most proximal determinant of this sensitivity. A related conclusion can be drawn from mediation analyses of survey data (Reviewed in [ 22 ] and [ 83 ]). These mediation studies show that multiple adverse states (including, stress, depression, anxiety, financial strain, antisocial behavior, bullying, intimate partner violence, intimate partner sexual coercion, childhood physical/sexual/emotional abuse, childhood trauma and adult trauma) are all associated with dependence severity, and this relationship is mediated by self-reported use of drugs to cope with negative affect.…”
Section: Relative Value Of Drugs Versus Alternative Rewards Underpinsmentioning
confidence: 92%
See 1 more Smart Citation
“…Mood induced drug choice was more replicably associated with coping motives than with dependence severity or psychiatric symptoms, suggesting that coping motives is the most proximal determinant of this sensitivity. A related conclusion can be drawn from mediation analyses of survey data (Reviewed in [ 22 ] and [ 83 ]). These mediation studies show that multiple adverse states (including, stress, depression, anxiety, financial strain, antisocial behavior, bullying, intimate partner violence, intimate partner sexual coercion, childhood physical/sexual/emotional abuse, childhood trauma and adult trauma) are all associated with dependence severity, and this relationship is mediated by self-reported use of drugs to cope with negative affect.…”
Section: Relative Value Of Drugs Versus Alternative Rewards Underpinsmentioning
confidence: 92%
“…show greater baseline drug choice) and should be more sensitive to acute negative mood induced increases in drug choice (because these individuals have learned, and verbally report, that the drug mitigates negative affect) [ 22 ]. Although self-reported substance use to cope with negative affect is closely associated with psychiatric symptoms, coping motives are thought to proximally mediate drug consumption decisions [ 82 , 83 ]. If this is true, we would expect coping motives to be more reliably associated with drug choice, and negative mood induced drug choice, than psychiatric symptoms.…”
Section: Relative Value Of Drugs Versus Alternative Rewards Underpinsmentioning
confidence: 99%
“…During disaster situations, some authors suggest that substance use could be a dysfunctional coping strategy in vulnerable populations ( Hogarth, Martin & Seedat, 2019 ). Evidence from the severe acute respiratory syndrome (SARS) outbreak showed that people used alcohol as a coping method ( Wu et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SSADDA, similar to the SSAGA, includes detailed questions on the onset and recency of criteria for individual substances and evaluates the criteria’s temporal clustering [4]. In contrast to the SSAGA, the SSADDA also includes sections on attention deficit hyperactivity disorder, gambling disorder, and childhood experiences [4], which have been shown to affect the risk of alcohol and drug use [8, 9].…”
Section: Introductionmentioning
confidence: 99%